Teacher collaboration: 30 years of research on its nature, forms, limitations and effects - Hargreaves, Andy (Teachers and teaching, theory and practice, 2019)
This article reprises and reflects on 30 years of the author's work on teacher collaboration. The distinctive nature of this work has not been in making a case for teacher collaboration in terms of its benefits for students, teachers, or educational change. These arguments are widely available elsewhere. Rather it has examined ways of collaborating that are available to teachers, how formal or informal collaboration should be, how collaborative efforts can be misused or misdirected, and what factors must be considered when deliberately designing teacher collaboration so it will have the most beneficial effects. The article discusses the explanatory and strategic power of three concepts in particular-contrived collegiality, professional capital, and collaborative professionalism. Conclusions are drawn about next steps for educational research in terms of establishing clear typologies of teacher collaboration in relation to their impact and appropriateness in different circumstances.